PENGARUH EMPLOYER BRANDING, MEDIA SOSIAL, DAN PERSEPSI TERHADAP NIAT MELAMAR KERJA PADA INDUSTRI STARTUP - Purwanto, Teguh; Salamah, Nailis; Yusuf, Muh (Neraca, 2023)
This research aims to determine the effect of employer branding, social media, and perceptions on job application intentions in the startup industry. The research method used is quantitative research method. The population used in this research was 541 students of Universitas Muhammadiyah Pekajangan Pekalongan. The sample used was 94 students using purposive sampling technique. Data collection techniques were carried out by distributing questionnaires and literature studies. The analysis technique used in this research is multiple linear regression analysis using the SPSS version 22 programme. The results of this research indicate that employer branding partially has no significant effect on job application intentions. Social media partially has a significant influence on job application intentions. Perception partially has a significant influence on job application intentions. Employer branding, social media, and perceptions simultaneously have a significant effect on job application intentions.